Recent Advances of Transition Metal Basic Salts for Electrocatalytic Oxygen Evolution Reaction and Overall Water Electrolysis - Guo, Bingrong; Ding, Yani; Huo, Haohao; Wen, Xinxin; Ren, Xiaoqian; Xu, Ping; Li, Siwei (Nano-Micro Letters, 2023)
Electrocatalytic oxygen evolution reaction (OER) has been recognized as the bottleneck of overall water splitting, which is a promising approach for sustainable production of H2. Transition metal (TM) hydroxides are the most conventional and classical non-noble metal-based electrocatalysts for OER, while TM basic salts [M2+(OH)2-x(Am−)x/m, A = CO32−, NO3−, F−, Cl−] consisting of OH− and another anion have drawn extensive research interest due to its higher catalytic activity in the past decade. In this review, we summarize the recent advances of TM basic salts and their application in OER and further overall water splitting. We categorize TM basic salt-based OER pre-catalysts into four types (CO32−, NO3−, F−, Cl−) according to the anion, which is a key factor for their outstanding performance towards OER. We highlight experimental and theoretical methods for understanding the structure evolution during OER and the effect of anion on catalytic performance. To develop bifunctional TM basic salts as catalyst for the practical electrolysis application, we also review the present strategies for enhancing its hydrogen evolution reaction activity and thereby improving its overall water splitting performance. Finally, we conclude this review with a summary and perspective about the remaining challenges and future opportunities of TM basic salts as catalysts for water electrolysis. Highlights: 1 We summarize the recent advances of transition metal basic salts and their application in oxygen evolution reaction (OER) and further overall water splitting. 2 The structure evolution of transition metal basic salts during OER and the impact of F−, Cl−, CO32− and NO3− on the OER performance are highlighted